2018
DOI: 10.18632/oncotarget.25133
|View full text |Cite
|
Sign up to set email alerts
|

Acquired resistance to everolimus in aromatase inhibitor-resistant breast cancer

Abstract: We previously reported the establishment of several types of long-term estrogen-depleted-resistant (EDR) cell lines from MCF-7 breast cancer cells. Type 1 EDR cells exhibited the best-studied mechanism of aromatase inhibitor (AI) resistance, in which estrogen receptor (ER) expression remained positive and PI3K signaling was upregulated. Type 2 EDR cells showed reduced ER activity and upregulated JNK-related signaling. The mTOR inhibitor everolimus reduced growth in cells similar to Type 1 EDR cells. The presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…[80][81][82][83][84][85][86] These aberrations associated with targeted therapy resistance could be used to develop an effective treatment sequence to delay disease progression. The majority of patients with advanced or ER-positive MBC will be treated with a CDK4/6 or mTOR inhibitor in combination with ET during the course of their disease.…”
Section: Preclinical Strategies To Identify Actionable Targets In Esrmentioning
confidence: 99%
See 1 more Smart Citation
“…[80][81][82][83][84][85][86] These aberrations associated with targeted therapy resistance could be used to develop an effective treatment sequence to delay disease progression. The majority of patients with advanced or ER-positive MBC will be treated with a CDK4/6 or mTOR inhibitor in combination with ET during the course of their disease.…”
Section: Preclinical Strategies To Identify Actionable Targets In Esrmentioning
confidence: 99%
“…Indeed, several studies now demonstrate differential mechanisms of acquired resistance to either mTOR or CDK4/6 inhibitors in breast and other cancers, including upregulation of MAPK signaling in everolimus-and palbociclib-resistant models, as well as mutations in RB1, and upregulation of CDK2, CCNE1, or PDK1 in palbociclib-resistant cells. [80][81][82][83][84][85][86] These aberrations associated with targeted therapy resistance could be used to develop an effective treatment sequence to delay disease progression. Certainly, several recent and ongoing clinical trials testing investigational agents are recruiting patients who have been treated previously with mTOR or CDK4/6 inhibitors, and comparison of response between these patient populations is necessary to provide insight into whether certain patient populations benefit from sequencing of targeted therapies or are inherently resistant to therapy.…”
Section: Preclinical Strategies To Identify Actionable Targets In Esrmentioning
confidence: 99%
“…Clinically, hormonal therapy resistance is considered a critical problem and is correlated with the involvement of intracellular phosphorylation pathways, such as the PI3K–AKT–mTOR pathway and MAPK pathways [7, 8]. Previously, we reported that driver signaling escapes to MAPK signaling despite the suppression of mTOR signaling [9]. Because of this, breast cancer cells struggle to survive by altering the driver pathway.…”
Section: Introductionmentioning
confidence: 99%
“…The acquired resistance to mTORC1 inhibitors was attributed to compensatory feedback loops involving the activation of oncogenes such as Myc , the upregulation of which is mediated by the transcriptional regulator bromodomain-containing protein 4 (BRD4) [33]. Recently, Kimura and colleagues studied everolimus-resistant cells generated from two cell lines resistant to AIs: the first had upregulated PI3K/AKT/mTOR signaling and constitutive ER overexpression; the second had low ER expression and upregulated receptor tyrosine kinase/c-jun N-terminal kinase (RTKs/JNK) signaling [34]. Both cell lines received long-term exposure to everolimus in vitro.…”
Section: Pi3k/akt/mtor Pathwaymentioning
confidence: 99%
“…Preclinical and clinical studies showed that PI3K/AKT/mTOR pathway inhibition has a synergistic effect with endocrine therapies, and could reduce tumor progression in HR+ PI3K mutant BCs beyond the first endocrine line of treatment [34,38,39]. The BELLE-2 trial was a phase III, double-blind, placebo-controlled randomized study that included women with HR+/HER2− MBC, whose diseases progressed on or after endocrine treatment with an AI (Table 1) [40].…”
Section: Pi3k/akt/mtor Pathwaymentioning
confidence: 99%